Tanggung Jawab PT Pos Indonesia (Persero) Terhadap Pengiriman Barang ke Luar Negeri - I Gusti Ngurah Gede Maheshwara Wedananta; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2025)
Overseas freight forwarding is the stage of sending goods across borders after complying with a set of rules and regulations. This process involves the service of sending goods or documents from one country to another, and involves a variety of rules, requirements and obstacles that can arise. This research discusses the rules and regulations related to the overseas shipment of goods and the responsibilities of PT Pos Indonesia (Persero) in the process. The results show that the shipment of goods abroad is regulated by Law Number 38 of 2009 concerning postal operations. In addition, Government Regulation No. 15 of 2013 regarding the implementation of the Act aims to improve postal services as a means of communication and information. Another relevant regulation is the Regulation of the Minister of Trade of the Republic of Indonesia Number 44/M-DAG/PER/7/2012 which stipulates goods that are prohibited from being exported. During the shipping process, PT Pos Indonesia has responsibility for the safety and completeness of the goods sent, including the compensation claim process that can be carried out by the sender as the legal owner of the goods sent.